2015
DOI: 10.1086/682428
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and Transverse Right Ventricular Function in Pulmonary Hypertension: Cardiovascular Magnetic Resonance Imaging Study from the ASPIRE Registry

Abstract: Right ventricular (RV) function is a strong predictor of outcome in cardiovascular diseases. Two components of RV function, longitudinal and transverse motion, have been investigated in pulmonary hypertension (PH). However, their individual clinical significance remains uncertain. The aim of this study was to determine the factors associated with transverse and longitudinal RV motion in patients with PH. In 149 treatment-naive patients with PH and 16 patients with suspected PH found to have mean pulmonary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Evidence suggests that RV longitudinal component measured by TAPSE is markedly reduced in post-cardiac surgery patients despite the absence of global RV ejection fraction decrease [17]. Recent studies with MRI suggest that RV function is reflected better by radial rather than longitudinal wall displacement in pulmonary hypertension patients [18, 19]. Pettersen and coworkers demonstrated that, after the Senning procedure (which transforms the RV to the systemic pump of the circulation), the patients have more pronounced radial component of RV function [20].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that RV longitudinal component measured by TAPSE is markedly reduced in post-cardiac surgery patients despite the absence of global RV ejection fraction decrease [17]. Recent studies with MRI suggest that RV function is reflected better by radial rather than longitudinal wall displacement in pulmonary hypertension patients [18, 19]. Pettersen and coworkers demonstrated that, after the Senning procedure (which transforms the RV to the systemic pump of the circulation), the patients have more pronounced radial component of RV function [20].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging (MRI) has emerged as a reliable and reproducible imaging method for assessing right heart morphology and function [6,7], including ejection fraction [31], longitudinal shortening [32], mass index [31] and work [33]. Of these parameters, ejection fraction, as assessed by cardiac MRI, has a strong prognostic value [31,34], with low right ventricular ejection fraction (RVEF) (<35%) being associated with poor survival, independent of PVR, and increases in RVEF after 12 months being predictive of improved 6-year survival [34].…”
Section: Echocardiography and Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Retrospectively ECG gated cardiac cine imaging in the two and four chamber views allow for qualitative and quantitative assessment of the structure and function of the ventricles [57]. Segmentation of the ventricular endocardium quantifies the right and left ventricular end-diastolic and end-systolic volumes from which stroke volume and ejection fraction can be calculated.…”
Section: Cardiac Cine Mr Imagingmentioning
confidence: 99%